Copper-catalyzed asymmetric sp3 C–H arylation of tetrahydroisoquinoline mediated by a visible light photoredox catalyst - Querard, Pierre; Perepichka, Inna; Zysman-Colman, Eli; Li, Chao-Jun (Beilstein Journal of Organic Chemistry, 2016)
This report describes a highly enantioselective oxidative sp3 C–H arylation of N-aryltetrahydroisoquinolines (THIQs) through a dual catalysis platform. The combination of the photoredox catalyst, [Ir(ppy)2(dtbbpy)]PF6, and chiral copper catalysts provide a mild and highly effective sp3 C–H asymmetric arylation of THIQs.
Keywords: C–H arylation; copper catalyst; enantioselectivity; visible light